Financial sector structure and financial crisis burden: A model based on the Russian default of 1998 - George Mavrotas; Dmitri Vinogradov (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
We consider an overlapping generations model with two production factors and two types of agents in the presence of financial intermediation and its application to the Russian default of August 1998. The paper focuses on the analysis of the consequences of a sudden negative repayments shock on financial intermediation capacity and consequently on the economy as a whole. The model exhibits a `chain reaction' property, when a single macroeconomic shock can lead to the exhaustion of credit resources and to the subsequent collapse of the whole banking system. To maintain the capability of the system to recover, regulatory intervention is needed even in the presence of the state guarantees on agents' deposits in the banks (workout incentives). We compare the results for an intermediated economy with those derived under the assumption of a market economy, and draw some broad conclusions on the consequences of the crises, which are contingent on the financial sector structure.
Keywords: D50; G21; G28; E44; E53; O16; 330; financial intermediation; banks; markets; overlapping generations models; general equilibrium; regulation; transition economies; financial crisis; Russian default; Finanzsektor; Finanzintermediär; Overlapping Generations; Russland; Finanzmarktkrise